FRI0084 SAFETY, PHARMACOKINETICS, PHARMACODYNAMICS, IMMUNOGENICITY, AND PRELIMINARY EFFICACY OF ROZIBAFUSP ALFA IN SUBJECTS WITH RHEUMATOID ARTHRITIS: INTERIM ANALYSIS OF A PHASE 1B RANDOMIZED, PLACEBO-CONTROLLED, MULTIPLE ASCENDING DOSE CLINICAL TRIAL. (2nd June 2020) - Abuqayyas, L.; Cheng, L.; Mitragotri, D.; Smith, S.; Teixeira Dos Santos, M.; Zhou, Y.; Chindalore, V.; Cohen, S.; Kivitz, A.; Posch, M.; Sullivan, B.; Parnes, J.
Abstract : Background: Autoimmune diseases, including systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), are associated with autoantibody production and dysregulated T- and B-cell responses. Rozibafusp alfa (AMG 570) is a first-in-class bispecific antibody-peptide conjugate targeting T- and B-cell activity through inhibition of ICOSL and BAFF and is currently in phase 2 clinical development for the treatment of SLE. Objectives: This interim analysis of a phase 1b study (NCT03156023 ) reports the safety, pharmacokinetics (PK), pharmacodynamics (PD), immunogenicity, and preliminary efficacy of rozibafusp alfa in subjects with RA. Methods: Subjects (N 34; age 18–75 years) with active RA, defined as a disease activity score (DAS28-CRP) >2.6, were randomized 3:1 to receive rozibafusp alfa or placebo subcutaneously every 2 weeks for 10 weeks (6 doses), with 24 weeks of follow-up. Subjects were divided into 4 cohorts to study 4 ascending doses of rozibafusp alfa. All subjects were maintained on a stable dose of methotrexate. The primary endpoint was the subject incidence of treatment-emergent adverse events (TEAEs). Additional assessments included serum PK profiles, PD (eg, ICOSL receptor occupancy [RO], changes in peripheral blood B cells), incidence of anti-rozibafusp alfa antibodies, and Patient and Physician Global Assessments (PtGA and PhGA) of disease activity. Results: As of June 5, 2019, 34 subjects were enrolled and included in this interim analysis. Rozibafusp alfa was generally well tolerated. TEAEs occurred in 92.3% and 87.5% of subjects receiving rozibafusp alfa and placebo, respectively. Most of these events were of grade ≤2 severity. The most common TEAE was upper respiratory infection (23.1%) for subjects receiving rozibafusp alfa and nasopharyngitis (37.5%) for subjects receiving placebo. No treatment-related AEs were of grade ≥3 severity and occurred in >2 subjects. Rozibafusp alfa demonstrated a nonlinear PK profile with greater than a dose-proportional increase in concentration across evaluated doses. The terminal half-life of rozibafusp alfa ranged from 5 to 11 days, with longer half-lives at higher dose levels. ICOSL RO on circulating B-cells was dose-related and reversible; upon multiple dosing, >90% mean RO was observed in cohorts 3 and 4. Treatment with rozibafusp alfa reduced the percentage of naïve B-cells and increased the percentage of memory B-cells in all cohorts. As of March 22, 2019, 2 of 18 (11.1%) rozibafusp alfa-treated subjects developed anti-rozibafusp alfa antibodies with no correlation to safety or AEs. Preliminary analysis of disease-related activity showed a trend for greater numerical improvement from baseline in PtGA and PhGA with rozibafusp alfa vs. placebo in cohorts 3 and 4. Conclusion: This interim analysis is the first to report the safety and tolerability of multiple ascending doses of rozibafusp alfa in RA subjects, with preliminary efficacy findings observed in the highest dose cohorts. PK/PD analysis demonstrated nonlinear, target-mediated disposition consistent with cell surface target interaction and PD activity consistent with dual ICOSL/BAFF neutralization. These findings informed the design and dose selection of an ongoing phase 2, randomized, placebo-controlled study to assess the efficacy and safety of rozibafusp alfa in subjects with active SLE and inadequate responses to standard of care therapy. Acknowledgments: Amgen Inc. and AstraZeneca sponsored this phase 1b study Disclosure of Interests: Lubna Abuqayyas Shareholder of: Stockholder of Amgen Inc., Employee of: Employee of Amgen Inc., Laurence Cheng Shareholder of: Stockholder of Amgen Inc., Employee of: Former employee of Amgen Inc., Deepali Mitragotri Shareholder of: Stockholder of Amgen Inc., Employee of: Employee of Amgen Inc., Shawna Smith Shareholder of: Stockholder of Amgen Inc., Employee of: Employee of Amgen Inc., Marcia Teixeira dos Santos Shareholder of: Stockholder of Amgen Inc., Employee of: Employee of Amgen Inc., Yanchen Zhou Shareholder of: Stockholder of Amgen Inc., Employee of: Employee of Amgen Inc., Vishala Chindalore Grant/research support from: Nektar Therapeutics for conducted studies, Speakers bureau: > 5 years ago, Stanley Cohen Grant/research support from: Grant and research support from Amgen, AbbVie, Pfizer, Genentech, and Lilly, Consultant of: Consultant for Amgen, AbbVie, Pfizer, Genentech and Lilly, Alan Kivitz Shareholder of: AbbVie, Amgen, Gilead, GSK, Pfizer Inc, Sanofi, Consultant of: AbbVie, Boehringer Ingelheim, , Flexion, Genzyme, Gilead, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi, SUN Pharma Advanced Research, UCB, Paid instructor for: Celgene, Genzyme, Horizon, Merck, Novartis, Pfizer, Regeneron, Sanofi, Speakers bureau: AbbVie, Celgene, Flexion, Genzyme, Horizon, Merck, Novartis, Pfizer Inc, Regeneron, Sanofi, Maximilian Posch: None declared, Barbara Sullivan Shareholder of: Shareholder of Amgen Inc., Employee of: Former employee of Amgen Inc. Current employee of Ultragenyx, Jane Parnes Shareholder of: Stockholder of Amgen Inc., Employee of: Employee of Amgen Inc.